Effect of Phosphate Solubilizing Bacteria on Phosphatase Activities, Yield and Phosphorus Nutrition of Wheat in an Acidic Entisol - A.K. Sinha, P. Mukhopadhyay and Y.V. Singh, Deepranjan Sarkar*, S. Rakesh (Journal of the Indian Society of Soil Science, 2022)
This research aims to determine the short-term prospects of phosphate solubilizing bacteria (PSB) application on growth and yield of wheat and fertility status of soil with special reference to phosphorus (P). Spectrophotometric analyses were carried out to determine acid phosphatase (APase) and alkaline phosphatase (ALPase) activities in plant roots and rhizosphere soil, P bioavailability at the salient growth stages and harvest of the wheat crop, and P nutrition at maturity. Results of the wheat field experiment conducted during winter 2014-15 showed that application of PSB significantly increased the root APase but a quite opposite trend of the APase activity between plant roots and rhizosphere soil was found. In the case of ALPase activity, the effect of PSB was more prominent in root than soil. Among the two enzymes (APase and ALPase), APase activity was constantly higher in root and soil, indicating its importance in P hydrolysis and plant nutrition under acidic and P deficient soil conditions. The combined application of P-fertilizer and PSB had a profound influence on soil available P. Considerable effect of PSB on yield could be noted, but no significant effect was observed for P nutrition. The research work clearly indicated the importance of integration of P-fertilizer and PSB for maintaining higher crop productivity and better soil fertility. The study also emphasizes the need to consider the determinants which modulate the effectiveness of PSB in P solubilization and plant growth promotion.